Rodinný dům - Kvet, Juraj (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Projekt rieši novostavbu rodinného domu v Brne časť Soběšice. Rodinný dom je určený pre 4 člennú rodinu pre celoročné bývanie. Stavba je navrhnutá približne do pôdorysného tvaru písmena „L“. Je to dvojpodlažný podpivničený objekt. Do ulice a do dvora sú situované terasy. Súčasťou je garáž určená pre jedno vozidlo. Nosný systém je riešený z keramických tvárnic Porotherm plnených minerálnou vatou. Konštrukcia strechy je plochá jednoplášťová. Pozemok je v mierne svažitom teréne.

The project deals with new building of detached in Brno, part Soběšice. Family house is designed for a family of four to year-round living. The building is designed to approximately in the shape of the letter „L“. It is a two-storey building with basement. Terraces are located to the backyard and to the street. Includes a garage designed for one vehicle. The supporting system object is solved from ceramic blocks Porotherm filled with mineral wool. The construction of the roof is flat, single. Land is in slightly sloping terrain.
Family House
Keywords: Rodinný dom; terasa; garáž; svah; keramické tvárnice; plochá strecha; suterén; Family house; terrace; garage; slope; ceramic blocks; flat roof; basement